Should Poland join the euro area? The challenge of the boom-bust cycle - Karnowski, Jakub; Rzońca, Andrzej (Publishing House of Wroclaw University of Economics and Business, 2023)
The article makes references to the existing cost-benefit analyses on adopting the euro in Poland and other new member states of the EU. In general, they considered a decrease in the cost of capital to be among the crucial benefits of adopting the common currency. As a result, the costs of a credit boombust cycle, to which adoption of the euro may lead, were at best underestimated. The authors discussed the possible solutions to mitigate the risk of boom-bust cycles and concluded that although they are conceptually simple, their effective implementation may be difficult, mostly due to political pressures. To overcome the feasibility problem, the power over undertaking macro prudential measures should be delegated to the central bank. Its past performance in stabilising the economy (at least until recently) suggests that it could make a good use of such a power. Furthermore, adopting the euro would resolve the problem of the ‘difficult cohabitation’ of monetary and macro prudential policy that such a delegation would otherwise create.
Argumenta Oeconomica, 2023, Nr 1 (50), s. 227-262
Keywords: euro adoption; boom-bust cycle; macro prudential measures